Multilingual education of students on a global scale and perspective - international networking on the example of bioindication and biomonitoring (B&B technologies). - Markert, Bernd (2014)
Living or formerly living organisms are being used to obtain information on the quality of the general health status of our environment by bioindication and biomonitoring methods for many decades. Thus, different roads toward this common scientific goal were developed by a lot of different international research groups. Global cooperation in between various scientific teams throughout the world has produced common ideas, scientific definitions, and highly innovative results of this extremely attractive working field. The transdisciplinary approach of different and multifaceted scientific areas—starting from biology, analytical chemistry, via health physics, up to social and economic issues—have surpassed mental barriers of individual scientists, so that “production” of straightforward common results related to the influence of material and immaterial environmental factors to the well-being of organisms and human life has now reached the forefront of international thinking. For the further sustainable development of our common scientific “hobby” of bioindication and biomonitoring, highest personal energy has to be given by us, being teachers to our students and to convince strategically decision makers as politicians to invest (financially) into the development of education and research of this innovative technique. Young people have to be intensively convinced on the “meaning” of our scientific doing, e.g., by extended forms of education. One example of multilingual education of students on a global scale and perspective is given here, which we started about 3 years ago.